Sie sind die Antwort auf alles - Haddix, Margaret Peterson,Münch, Bettina (Dt. Taschenbuch-Verl., 1999)
After joining her new friends in the religious group called Fishers of Men, Dorry finds herself caught up in a cult from which she must struggle to extricate herself.
Keywords: Jugendbuch; Christian life; Cults; Fanaticism; Strafe; Wohnungswechsel; Unsicherheit; Mädchen; Befreiung; Einsamkeit; Sekte; Zwang; Religion